Siglec-G Deficiency Ameliorates Hyper-Inflammation and Immune Collapse in Sepsis via Regulating Src Activation - Li, Wenqian; Li, Yinjiao; Qin, Kewei; Du, Boxiang; Li, Tianliang; Yuan, Hongbin; Han, Chaofeng; Luo, Yan (Frontiers in Immunology, 2019)
Hyper-inflammation during acute phase and sequential hypo-inflammation during immunosuppressive phase in macrophages/monocytes lead to multi-organ failure syndrome and immune collapse of sepsis, in which Toll-like receptor (TLR)-triggered inflammatory responses play a major role. Here we reported that Siglecg deficiency attenuated TLR4-triggered pro-inflammatory cytokine production and increased anti-inflammatory cytokine (interleukin-10, IL-10) production in vivo and in vitro at both acute and immunosuppressive phases. Siglecg deficiency also protected mice from LPS-induced sepsis with less inflammation in lung and less tissue destruction in spleen. Siglec-G inhibited proto-oncogene tyrosine-protein kinase Src (Src) activation via recruiting and activating tyrosine phosphatase Src homology region 2 domain-containing phosphatase-1 (SHP1) through immunoreceptor tyrosine-based inhibitory motif (ITIM) domain. Src could inhibit TLR4-induced inflammatory cytokines and promote anti-inflammatory cytokine IL-10. Mechanical investigation showed that Src could interact with and phosphorylate STAT3. Src could also promote HIF1α degradation through activating GSK3β. Our study reveals that Siglec-G orchestrates TLR-induced inflammation, which outlines that blocking Siglec-G or activating Src may be a promising strategy for both acute and chronic inflammatory diseases.